A Decision Support System for Selecting Outstanding Village Officials Using the Analytical Hierarchy Process (AHP): A Case Study of Pajar Bulan Village - GILANG ZULBAHRI; NURUL ADHA OKTARINI SAPUTRI (Institute of Information Technology and Social Science (IITSS), 2024)
Law Number 06 of 2014 concerning Villages stipulates that the authority to appoint and dismiss village officials is vested in the village head, provided that the process complies with prevailing legal regulations. Consequently, the selection of outstanding village officials must be conducted in a fair, transparent, and accountable manner to avoid subjectivity and bias. This study aims to design and implement a Decision Support System (DSS) for selecting the best village officials at the Pajar Bulan Village Office by applying the Analytical Hierarchy Process (AHP) method. AHP is utilized as a structured multi-criteria decision-making approach that determines priority weights through systematic pairwise comparisons. The proposed system was developed using the PHP programming language with a MySQL database as the data storage platform. The results demonstrate that the system is capable of producing objective and accurate rankings of village officials based on predetermined criteria, thereby enhancing both the efficiency and transparency of the selection process at Pajar Bulan Village.